Does early communication mediate the relationship between motor ability and social function in children with cerebral palsy?. (June 2016) - Lipscombe, Belinda; Boyd, Roslyn N.; Coleman, Andrea; Fahey, Michael; Rawicki, Barry; Whittingham, Koa
Abstract: Background: Children diagnosed with neurodevelopmental conditions such as cerebral palsy (CP) are at risk of experiencing restrictions in social activities negatively impacting their subsequent social functioning. Research has identified motor and communication ability as being unique determinants of social function capabilities in children with CP, to date, no research has investigated whether communication is a mediator of the relationship between motor ability and social functioning. Aims: To investigate whether early communication ability at 24 months corrected age (ca.) mediates the relationship between early motor ability at 24 months ca. and later social development at 60 months ca. in a cohort of children diagnosed with cerebral palsy (CP). Method: A cohort of 71 children (43 male) diagnosed with CP (GMFCS I = 24, 33.8%, II = 9, 12.7%, III = 12, 16.9%, IV = 10, 14.1%, V = 16, 22.5%) were assessed at 24 and 60 months ca. Assessments included the Gross Motor Function Measure (GMFM), the Communication and Symbolic Behaviour Scales-Developmental Profile (CSBS-DP) Infant-Toddler Checklist and the Paediatric Evaluation of Disability Inventory (PEDI). A mediation model was examined using bootstrapping. Results: Early communication skills mediated the relationship between early motor abilities and later social functioning, b = 0.24 (95% CI = 0.08–0.43 and the mediation model was significant, F (2, 68) = 32.77, p < 0.001, R 2 = 0.49. Conclusions and implication: Early communication ability partially mediates the relationship between early motor ability and later social function in children with CP. This demonstrates the important role of early communication in ongoing social development. Early identification of communication delay and enriched language exposure is crucial in this population.